The Effect of E-Leadership and Telework Ability towards Employee Performance of PT. Pelabuhan Indonesia (Persero) Regional II Cirebon - Nutrisari, Ayu; Kurniawan, Pebi; Jufri, Ali; Nurjannah, Khalifah (Dinasti Publisher, 2024)
This study aims to test and determine whether e- leadership and telework ability put some effects towards employee performance. The research method used is a quantitative method. This study used non-probability sampling with saturated sampling towards 82 respondents. The data analysis technique used in this research is multiple linear regression analysis techniques and to measure research variables, researchers use a Likert Scale. The results of data analysis show that e-leadership consisting of visionary, convener, team sponsor, manager, innovator and mentor has an effect towards the performance of employees of PT Pelabuhan Indonesia (Persero) Regional II Cirebon. Meanwhile, the data shows that telework ability which consists of knowledge, skills and attitudes also has an effect on employee's performance. However, if further tested together the e-leadership and telework ability variables above have positive and significant effects on the performance of employees of PT. Pelabuhan Indonesia (Persero) Regional II Cirebon.